2019
DOI: 10.1126/sciadv.aax0780
|View full text |Cite
|
Sign up to set email alerts
|

Drug-encapsulated carbon (DECON): A novel platform for enhanced drug delivery

Abstract: Current drug-delivery systems are designed primarily for parenteral applications and are either lipid or polymer drug conjugates. In our quest to inhibit herpes simplex virus infection via the compounds found in commonly used cosmetic products, we found that activated carbon particles inhibit infection and, in addition, substantially improve topical delivery and, hence, the efficacy of a common antiviral drug, acyclovir (ACV). Our in vitro studies demonstrate that highly porous carbon structures trapped virion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Restasis®from Allergan (Irvine, CA, USA) is a 0.05% CyA anionic emulsion, containing castor oil and polysorbate 80 as emulsifying agent, and was launched on the United States market before 2012, while Ikervis®(Santen Oy, Tampere, Finland), a 0.1% CyA stable cationic nanoemulsion based on Nanosorb®technology, was granted marketing authorisation by the European Commission (EC) for treatment of severe keratitis in adult patients with DED only after 2015. These commercial products result from many attempts done by using different strategies, still in continuous development, such as prodrugs [12], liposomes [13], nanoparticles [14], nanosphere [15], solid lipid nanoparticles [16][17][18], contact lenses [19], ocular inserts [20,21], implants [22] and emulgel [23]. Each of these techniques has contributed to solve various critical issues such as cytotoxicity, low precorneal residence time after ocular instillation with reduced bioavailability and low solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Restasis®from Allergan (Irvine, CA, USA) is a 0.05% CyA anionic emulsion, containing castor oil and polysorbate 80 as emulsifying agent, and was launched on the United States market before 2012, while Ikervis®(Santen Oy, Tampere, Finland), a 0.1% CyA stable cationic nanoemulsion based on Nanosorb®technology, was granted marketing authorisation by the European Commission (EC) for treatment of severe keratitis in adult patients with DED only after 2015. These commercial products result from many attempts done by using different strategies, still in continuous development, such as prodrugs [12], liposomes [13], nanoparticles [14], nanosphere [15], solid lipid nanoparticles [16][17][18], contact lenses [19], ocular inserts [20,21], implants [22] and emulgel [23]. Each of these techniques has contributed to solve various critical issues such as cytotoxicity, low precorneal residence time after ocular instillation with reduced bioavailability and low solubility.…”
Section: Introductionmentioning
confidence: 99%
“…This kinase inhibitor is being considered at par with trifluorothymidine (TFT), which is the currently prescribed therapeutic for ocular herpes (Jaishankar et al, 2018). Yadavalli et al (2019) have found activated carbon particles to be efficient acyclovir (ACV)-drug delivery systems that trapped the virions within themselves. Zinc oxide micro-nanoparticles and nanowires can inhibit HSV-1 entry as well (Antoine et al, 2012;Trigilio et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Yadavalli et al [133] have explored the potential of highly porous activated carbon (HPAC) particles as a model for restricting HSV-1 and HSV-2 from entering target cells. They have considered this material due to the charcoal surface-active that could provide antiviral effects through virion sequestration approach.…”
Section: Nano-based Antiviral Agents Against Herpes Virusesmentioning
confidence: 99%